The future of public employee retirement systems - Mitchell, Olivia S.; Anderson, Gary. (Oxford : Oxford University Press, 2009)
Public pensions are often the subject of 'pension envy', as their benefits might seem more generous and contributions lower than those in the private sector. This text shows that such judgments are often inaccurate, and reflects a vigorous debate amongst academics as they seek to define a new future for public retirement systems.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Civil service -- Pensions; Civil service -- Retirement; State governments -- Officials and employees -- Pensions -- United States; Local officials and employees -- Pensions -- United States; United States -- Officials and employees -- Pensions